(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Training with rubber ropes is one of the modern training methods that help to develop the absolute strength of specific parts of the body and according to the skill performance, especially when training with different muscle moments that cause the movement of those limbs according to variable resistances, especially for wheelchair tennis players, so the research was applied to a sample of tennis players with chairs Using these exercises to find out their effect on the serve skill mechanism, this exercises were applied for a period of (10) weeks, on (6) players who are the best players in this competition, and the researcher used foreign and Arab sources and the international information network, observation, experimentation, tests and measurements as means of collecting information. A video camera for filming and using kinematic analysis to extract the mechanical variables, and the researcher came up with several conclusions, including that training according to the results of the analysis and using the change of resistance arms when training with rubber ropes was effective in developing the speed of the centers of the striking arm parts of the research sample. The exercises led to an improvement in the technical performance interdependence (the research sample), which inevitably affected the achievement of good achievement, as well as in improving the response time of the research sample